Enterprise Resource Planning of Procurement Process with SAP MM Module - Dhuhadmya Anggiya Kirana; Muhardi Saputra; Warih Puspitasari (International Journal of Innovation in Enterprise System, 2021)
PT XYZ is one of the mining companies in Indonesia that has many subsidiaries. From userinterviews, there’s a problem in carrying out daily transactions in the procurement process. There isno integration between departments when using existing applications, lots of inappropriate data, andsome documents with missing files. Thus causing data not on time and working time. The analysiswas carried out using a conceptual model to see the problems and needs in PT XYZ. ERP systemneeds to be implemented, coordinating the company’s business processes and reset the company’sinfrastructure and standardization. The ERP system in the material management module will beimplemented using the ASAP method because this method is tailored to the company. The ASAPmethod can describe implementation activities to support project management and data migrationfaster than other implementation methods.